Quantum Learning Approach to Learning Quran During the Covid-19 Pandemic at SDIT LHI Yogyakarta - Muis , Abdul; Hamami , Tasman (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
The Al-Quran learning process requires effective approaches and methods, especially during the Covid-19 pandemic. Of course, many problems will be faced in online learning that is not in line with expectations. The quantum learning approach is an alternative solution in learning the Qur’an online during a pandemic. This study aims to elaborate on the process of learning the Koran with a quantum learning approach. This research makes an essential contribution to the development of effective Al-Quran learning. This study uses a phenomenological approach with a type of field study that focuses on a quantum learning approach during the Covid-19 pandemic. The data sources of this research were obtained through in-depth interview techniques, participatory observation, and documentation which were processed using Miles and Huberman’s interactive model. Based on the study of Al-Quran, learning using a quantum learning approach creates an active, innovative, and fun learning process. In the Al-Quran learning process, SDIT LHI applies seven stages of learning that are carried out systematically and coordinated, including opening, apperception, concept planting, understanding, skills or exercises, evaluation, and finally closing. The quantum learning approach plays a role in increasing the effectiveness of online Qur’an learning during the Covid-19 pandemic.